Clinical outcome and cost analysis of negative pressure wound therapy in extremity wounds: a comparison to conventional wound management - Khonglah, Tashi G.; Borgohain, Bhaskar; Khongwir, Wanlamkupar; Ahmed, Kashif A. (International Journal of Research in Orthopaedics, 2020)
Background: Open fractures and traumatic wounds constitute a major health problem. Amongst the armamentarium of wound care products available, negative pressure wound therapy (NPWT) is a modality that has transformed wound care and has been recommended for treating all kinds of acute and chronic wounds. Methods: This prospective randomised comparative study was conducted at a tertiary care hospital in Northeast India. 30 patients were included in this study over a period of 24 months commencing from January 2018. The patients consisted of two groups of 15 each, the first group comprised patients who underwent treatment using NPWT and the second group was treated using standard wound therapy (SWT). The endpoint taken was a granulated wound or a wound ready for split skin grafting (SSG). Results: The mean wound size difference between the NPWT group and the SWT group on day nine was 13±7.17 mm and 4.53±0.99 mm, respectively. Likewise, on day nine, 11 (73.3%) patients in the group treated using NPWT had no positive bacterial cultures compared to 8(53.3%) patients on SWT. The estimated cost of materials for each NPWT dressing change was roughly INR₹ 3446 (US$ 45.57). Conclusions: NPWT is not a magic bullet and will not replace the basic methods of wound treatment such as wound debridement, infection control and ensuring adequate blood supply. Nevertheless, NPWT remains an integral part of the current scenario in wound care management and is cost effective under the condition that it accelerates wound healing when compared to traditional treatment.